The new way things work - Macaulay, David, 1946-; Ardley, Neil, 1937-2004 (Houghton Mifflin, 1998)
"Text and numerous detailed illustrations introduce and explain the scientific principles and workings of hundreds of machines. Includes new material about digital technology."
Rev. and updated ed. of: The way things work, 1988
Obsahuje rejstřík
Keywords: technika; technology; populárně-naučné publikace; publikace pro mládež; popular works; juvenile literature